Institutional bypasses a strategy to promote reforms for development - Prado, Mariana Mota; Trebilcock, Michael J. 1941- (Cambridge University Press, 2018)
"Institutional bypass is a reform strategy that creates alternative institutional regimes to give citizens a choice of service provider and create a form of competition between the dominant institution and the institutional bypass. While novel in the academic literature, the concept captures practices already being used in developing countries. In this illuminating book, Mariana Mota Prado and Michael J. Trebilcock explore the strengths and limits of this strategy with detailed case studies, showing how citizen preferences provide a benchmark against which future reform initiatives can be evaluated, and in this way change the dynamics of the reform process. While not a 'silver bullet' to the challenge of institutional reform, institutional bypasses add to the portfolio of strategies to promote development. This work should be read by development researchers, scholars, policymakers, and anyone else seeking options on how to promote change and implement reforms in developing countries around the world"...